Bahrain Meaning in the Story of Musa and Khidr - Sa'dudin, Ihsan; Safitri, Eka; Akastangga, Muhammad Dedad Bisa Raguna; Huda, Nur; Mohamed Salem Alawadi, Elsayed (Universitas Islam Negeri Raden Intan Lampung, 2022)
In surah Al-Kahf verses 60-82, the term bahrain has a deeper connotation than its lexical sense. It is because the passage is linked to the story of Musa and Khidr. The two prophets reflect the several types of knowledge that the term bahrain encompasses. This research aims to examine and uncover the meaning of the word bahrain. This study employed a semiotic approach and a qualitative descriptive research method. The stages in analyzing the data are isytiqaq kabir, syntagmatic-paradigmatic, and semiotics analysis. Isytiqaq kabir was adopted to determine the denotative meaning of the Bahrain word. Syntagmatic-paradigmatic analysis was employed to explain the valence of the bahraini. Semiotics was adopted to analyze the signs in the verses that build meaning. Based on the isytiqaq kabir analysis, the term bahr signifies sea, honor, a prominent position, knowledge, benefit, and being generous. Meanwhile the result of syntagmatic-paradigmatic analysis, bahrain has two seas of knowledge: rational and intuitive knowledge. After going through three stages of linguistic analysis, Allah instructs Musa to learn from Khidr so that he can be wiser in dealing with his people. This research contributes to the treasures of new interpretations of the Qur'anic verses using linguistic concepts and theories.